Zdravljenje koronavirusne bolezni 19 z zdravili - Morgan, Tina (Farmacevtski vestnik, 2022)
The underlying pathophysiologic evolution of the disease from the predominantly viral infection-driven phase to the late, immune-mediated phase is important in the assessment of the role of medications against COVID-19. The best results can be expected from the orally used nirmatrelvir coformulated with ritonavir, the intravenously used remdesivir and the anti-SARS-CoV-2 monoclonal antibodies. The oral antiviral molnupiravir is less effective. When treating the fully developed disease, the most widely tested medications are dexamethasone and tocilizumab. Other anti-inflammatory treatments, baricitinib, tofacitinib or anakinra, have been shown to express very good clinical endpoints, which were however proven in a single clinical trial. The virus mutating to a variant less likely to cause typical presentation with severe immunological derangements probably will prevent us from gaining further knowledge in this area of therapeutics.
Keywords: anti-inflammatory medications; antiviral medications; Covid-19; Protivirusna zdravila; Protivnetna zdravila; SARS-CoV (virus); SARS-CoV-2; Terapija z zdravili